Fe1-xS/biochar combined with thiobacillus enhancing lead phytoavailability in contaminated soil: Preparation of biochar, enrichment of thiobacillus and their function on soil lead. (December 2020) - Ye, Junpei; Liao, Wenmin; Zhang, Panyue; Li, Juan; Nabi, Mohammad; Wang, Siqi; Cai, Yajing; Li, Fan
Abstract: Properly increasing mobility of heavy metals could promote phytoremediation of contaminated soil. Fe1-x S/biochar was successfully prepared from sawdust with loading pyrrhotite (Fe1-x S) at a pyrolysis temperature of 550 °C. Thiobacillus were successfully adsorbed and enriched on the surface of Fe1-x S/biochar. Microbial growth for 36 d supported by bio-oxidization of Fe1-x S decreased the system pH from 4.32 to 3.50, increased the ORP from 298 to 487 mV, and the Fe 3+ release reached 25.48 mg/g, enhancing the oxidation and leaching of soil Pb. Finally, Fe1-x S/biochar and Thiobacillus were simultaneously applied into Pb-contaminated soil for 60 d, the soil pH decreased from 7.83 to 6.72, and the exchangeable fraction of soil Pb increased from 22.86% to 37.19%. Ryegrass planting for 60 d in Pb-contaminated soil with Fe1-x S/biochar and Thiobacillus showed that the Pb content in shoot and root of ryegrass increased by 55.65% and 73.43%, respectively, confirming an obvious increase of phytoavailability of soil Pb. The relative abundance of Thiobacillus in remediated soil significantly increased from 0.06% to 34.55% due to the addition of Fe1-x S/biochar and Thiobacillus . This study provides a novel approach for regulating the Pb phytoavailability for phytoremediation of Pb-contaminated soil. Graphical abstract: Image 1 Highlights: Fe1-x S/biochar was simply prepared for in-situ phytoremediation of soil Pb. Fe1-x S/biochar supported Thiobacillus growth and improved bioavailability of soil Pb. Fe1-x S/biochar with Thiobacillus worked as acidic spots in Pb-contaminated soil.